2018
DOI: 10.1002/jlcr.3589
|View full text |Cite
|
Sign up to set email alerts
|

Automated production of [18F]FTHA according to GMP

Abstract: 14-(R,S)-[ F]fluoro-6-thia-heptadecanoic acid is a tracer for fatty acid imaging by positron emission tomography. High demand for this tracer required us to replace semiautomatic synthesis with a fully automated procedure. An automated synthesis device was constructed in-house for multistep nucleophilic F-fluorination and a control system was developed. The synthesis device was combined with a sterile filtration unit and both were qualified. 14-(R,S)-[ F]fluoro-6-thia-heptadecanoic acid was produced according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Perhaps the most promising long chain fatty acid analogue is 14(R,S)-18 F-fluoro-6-thia-heptadecanoic acid ( 18 F-FTHA) [27,28]. GMP production of this tracer was achieved in a good radiochemical yield of 13% [29]. Clinical studies are yet to be reported.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most promising long chain fatty acid analogue is 14(R,S)-18 F-fluoro-6-thia-heptadecanoic acid ( 18 F-FTHA) [27,28]. GMP production of this tracer was achieved in a good radiochemical yield of 13% [29]. Clinical studies are yet to be reported.…”
Section: Discussionmentioning
confidence: 99%
“…10 min), an intravenous injection of 18 F-FTHA was given and a dynamic emission scan was performed (frames: 1 × 60 s, 6 × 30 s, 1 × 60 s, 3 × 300 s, 2 × 600 s) on the same area as with radiowater. 18 F-FTHA was produced as previously described 33 , 34 .…”
Section: Methodsmentioning
confidence: 99%
“…[ 18 F]Fluoride was produced as reported previously . The initial amount of [ 18 F]F − used was 6.4 ± 2.5 GBq in the radiochemistry studies and 16.4 ± 1.5 GBq for A m determinations.…”
Section: Methodsmentioning
confidence: 99%
“…[ 18 F]Fluoride was produced as reported previously. 22 The initial amount of [ 18 F]F − used was 6.4 ± 2.5 GBq in the radiochemistry studies and 16.4 ± 1.5 GBq for A m determinations. The [ 18 F]KF solution was dried using azeotropic distillation with MeCN and Kryptofix K 222 (15.5-16.5 μmol) at 120°C with helium flow to form the dry [ 18 F]KF/K 222 complex.…”
Section: Radiochemistrymentioning
confidence: 99%